ANALYSIS OF INFLUENCER @SHABRINAALUNA'S STRATEGY IN MANAGING INSTAGRAM CONTENT TO BUILD FOLLOWERS' TRUST - Efri Ayu A. Br. Surbakti; Einggo Adinata; Ahmad Saleh Afif Siregar; Asri Widyanti; Agung Kurniawan Sastro (Jurnal Scientia, 2023)
This study aims to determine influencer marketing in managing Instagram content as an effort to build the trust of its followers. The type of research used is a qualitative approach, and data collection is in the form of semi-structured interviews, observation, and documentation. The results of this research influencer marketing manage content using four elements of value, namely; content management to communicate product quality through photos and details of the photo so that the quality and background for taking photos are also considered so that the quality and photos are appropriate. Build followers' trust through captions and usually to show promotions of the products or services represented, the value of ease of communicating through tags or mentions of the represented brand accounts, emotional factors communicating through honest reviews to increase customer loyalty and satisfaction.